The Influence Of Work Ethics And Work-Life Balance On Teacher Productivity At Athalia Junior High School - Silvia Anne Tioma M. Silaban; Fransiscus Amonio Halawa (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of work ethics and work-life balance on teacher productivity at Athalia Junior High School, South Tangerang. Employing a quantitative causal-associative approach with survey method, data were collected from 33 teachers as a saturated sample. A Likert scale (1–5) questionnaire was used to measure three variables: work ethics (X1), work-life balance (X2), and work productivity (Y). Data were analyzed using multiple linear regression via SPSS 27. Partial t-test results indicate that work ethics did not significantly influence productivity independently (t=1.680; p=0.103), whereas work-life balance had a positive and significant effect (t=4.519; p<0.001). Simultaneous F-test confirmed that both variables jointly exert a significant positive effect on teacher productivity (F=18.143; p<0.001). The coefficient of determination (Adjusted R²) of 51.7% demonstrates a substantial contribution. These findings suggest that school management policies should prioritize structured work-life balance programs to sustain long-term teaching effectiveness.